2021
DOI: 10.1021/acs.jafc.1c03379
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic Lipidomics Analysis Reveals the Ameliorative Effects of Highland Barley β-Glucan on Western Diet-Induced Nonalcoholic Fatty Liver Disease Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by marked imbalances in lipid storage and metabolism. Because the beneficial health effects of cereal β-glucan (BG) include lowering cholesterol and regulating lipid metabolism, BG may alleviate the imbalances in lipid metabolism observed during NAFLD. The aim of our study was to investigate whether BG from highland barley has an effect on western diet-induced NAFLD in mice. Using lipidomics, we investigated the underlying mechanisms of BG intervention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
4
22
0
Order By: Relevance
“…Additionally, in our previous study, it was found that HBG significantly unregulated the expressions of sterol 12α-hydroxylase (CYP8B1) and sterol 27-hydroxylase (CYP27A1). 30 Therefore, consistent with our hypothesis, these results suggest that HBG promotes the synthesis of BAs by activating both the classical and alternative pathways of BA synthesis, thus leading to cholesterol degradation.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, in our previous study, it was found that HBG significantly unregulated the expressions of sterol 12α-hydroxylase (CYP8B1) and sterol 27-hydroxylase (CYP27A1). 30 Therefore, consistent with our hypothesis, these results suggest that HBG promotes the synthesis of BAs by activating both the classical and alternative pathways of BA synthesis, thus leading to cholesterol degradation.…”
Section: Resultssupporting
confidence: 90%
“…All animal experiments were conducted as described in our previous study. 30 Five-week-old male C57BL/6 mice were housed under ambient conditions (temperature, 22 ± 2 °C; relative humidity, 55 ± 5%) using a 12 h alternate light/dark cycle. After a week of adaptive feeding, forty 5-week-old male mice (obtained from the Xi'an Jiaotong University Health Science Center) were randomly divided into 5 groups as follows: the normal diet group (ND group), in which the mice were fed with a standard diet of AIN-93M; the western diet group (WD group), in which the mice were fed with a western high-fat diet (42% kcal from fat, TP26300, obtained from Trophic Animal Feed High-Tech Co., Ltd, Nantong, China) and 4.2% sugar water (containing 18.9 g L −1 sucrose and 23.1 g L −1 fructose); the low-dose highland barley BG intervention group (WD + 100 mg per kg body weight highland barley BG, LBG group); the high-dose highland barley BG intervention group (WD + 300 mg per kg body weight highland barley BG, HBG group) and the positive control group (WD + 20 mg per kg body weight orlistat, PC group).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, an animal test demonstrated that mice fed barley (Hordeum vulgare; HV) combined β-glucan (BG) for 10 weeks diminished the area of liver brosis and decreased the expression level of transforming growth factor beta (TGFβ) 8 . Another report showed that the consumption of rich-BG can be hampered the fat absorption, leading to amelioration of NAFLD 9 .…”
Section: Introductionmentioning
confidence: 99%